Older and incarcerated: policy implications of aging prison populations. Issue 1 (13th March 2017) - Psick, Zachary; Simon, Jonathan; Brown, Rebecca; Ahalt, Cyrus
Abstract : Purpose: The purpose of this paper is to explore the policy Implications of aging prison populations. Design/methodology/approach: An examination of the worldwide aging trend in prison and its implications for correctional policy, including an examination of population aging in California prisons as a case example of needed reform. Findings: Prison populations worldwide are aging at an unprecedented rate, and age-related medical costs have had serious consequences for jurisdictions struggling to respond to the changes. These trends are accompanied by a growing body of evidence that old age is strongly correlated with desistance from criminal behavior, suggesting an opportunity to at least partially address the challenges of an aging prison population through early release from prison for appropriate persons. Originality/value: Some policies do exist that aim to reduce the number of older, chronically ill or disabled and dying people in prison, but they have not achieved that goal on a sufficient scale. An examination of the situation in California shows that recognizing how the healthcare needs of incarcerated people change as they age – and how aging and aging-related health changes often decrease an older person's likelihood of repeat offense – is critical to achieving effective and efficient policies and practices aimed at adequately caring for this population and reducing their numbers in prisons when appropriate.